Kegiatan Pendampingan Belajar Al Qur’an pada Anak-Anak Usia SD di TPQ Nurul Ummah Dusun Tunggulsari - Abdullah, Mu'in; Sulistyowati, Sulistyowati; Safitri, Yuni (LPMP Imperium, 2024)
Studying the Quran is a noble act in the eyes of Allah SWT. However, nowadays, many children, teenagers, and even adults prefer playing over learning the Quran, resulting in a gradual abandonment of Quranic education. Conversely, studying the Quran brings significant advantages and merits compared to other pursuits. Therefore, Quranic education activities have become a focal point of society, particularly for children who represent the future generation. This educational initiative will take place at the Nurul Ummah Quran Education Park in Tunggulsari hamlet, Pojok village, Mojogedang district, Karanganyar regency. The objectives of this activity are: To enhance children's proficiency in reading, writing, and memorizing the Quran correctly; To introduce the Quran to children from an early age; and To foster a comprehensive understanding of Islam. The mentoring will be conducted face-to-face using methods such as lectures, question-and-answer sessions, practice, and storytelling. The mentoring activities will be carried out in three stages: preparation, implementation, and evaluation. The final outcome of this service demonstrates that Quranic learning support has a positive impact on children's motivation and understanding of the Quran, as well as its benefits in their lives. This is evident through positive changes in children's behavior.